A Non-Pharmacologic Approach to Manage Behaviours in Confused Medically Ill Older Adults in Acute Care - Dasgupta, Monidipa (Can Geriatr J, 2021)
BACKGROUND: Non-pharmacological interventions are recommended to manage challenging behaviours among cognitively impaired older adults, however few studies have enrolled patients in acute care. This study aimed to determine the feasibility of implementing non-pharmacological interventions to manage behaviours in hospitalized older adults. METHOD: A self-identity approach was used to identify potentially engaging activities for 13 older medically ill adults admitted to acute hospital; these activities were trialed for a two-week period. Data were collected on frequency of intervention administration and assistance required, as well as frequency of behaviours and neuroleptic use in the seven days prior to and following the trial of activities. RESULTS: Per participant, 5–11 interventions were prescribed. Most frequently interventions were tried two or more times (46%); 9% were not tried at all. Staff or family assistance was not required for 27% of activities. The mean number of documented behaviours across participants was 4.8 ± 2.3 in the pre-intervention period and 2.1 ± 1.9 in the post-intervention period. Overall the interventions were feasible and did not result in increasing neuroleptic use CONCLUSION: Non-pharmacologic interventions may be feasible to implement in acute care. More research in this area is justified.